2011
DOI: 10.1007/s10439-011-0388-0
|View full text |Cite
|
Sign up to set email alerts
|

Photothermal Cancer Therapy and Imaging Based on Gold Nanorods

Abstract: Gold nanorods (GNRs), which strongly absorb near-infrared (NIR) light, have shown great potential in fields of biomedical application. These include photothermal therapy, molecular imaging, biosensing, and gene delivery, especially for the treatment of diseased tissues such as cancer. These biomedical applications of GNRs arise from their various useful properties; photothermal (nanoheater) properties, efficient large scale synthesis, easy functionalization, and colloidal stability. In addition, GNRs do not de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
121
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(124 citation statements)
references
References 86 publications
1
121
0
2
Order By: Relevance
“…The effectiveness of the method was determined by measuring changes in cell viability after laser irradiation of cells in the presence of GNRs. In accordance with other results in comparable experiments [12][13][14], ours indicated that continuous laser irradiation in the presence of the particles induced a significant decrease in cell viability, while no decrease in cell viability was observed with laser irradiation or incubation with GNRs alone [15].…”
Section: Introductionsupporting
confidence: 92%
“…The effectiveness of the method was determined by measuring changes in cell viability after laser irradiation of cells in the presence of GNRs. In accordance with other results in comparable experiments [12][13][14], ours indicated that continuous laser irradiation in the presence of the particles induced a significant decrease in cell viability, while no decrease in cell viability was observed with laser irradiation or incubation with GNRs alone [15].…”
Section: Introductionsupporting
confidence: 92%
“…The plasmonic properties of gold nanorods allow them to be used in photothermal therapy [1,2], imaging techniques [3,4], theranostics [5,6], sensing applications [7][8][9][10] and optical memories [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…The surface modification methods of GNRs include ligand exchange, layer-by-layer (LBL) and surface coating [14,15]. In ligand exchange method, some biological molecules, such as phosphatidylcholine (PC) [16], lipids [17] and thiol compounds, such as alkanethiol [18], thiol-terminated poly (ethylene glycol) (PEG-SH) [19], thiolated chitosan [20], were used to replace CTAB completely or at least partially.…”
Section: Surface Modifications Of Gnrsmentioning
confidence: 99%